The course of mechanical allodynia differs between forelimb innervation territories following median nerve injury in the rat - Ritter, Jana; Prahm, Cosima; Büttcher, Manuela; Wuttke, Thomas V.; Daigeler, Adrien; Lauer, Henrik; Heinzel, Johannes C.; Kolbenschlag, Jonas (Frontiers in Neuroscience, 2025)
Functional deficits and chronic neuropathic pain after peripheral nerve injuries pose major clinical challenges. For preclinical evaluation of novel treatments, reliable methods for assessing functional recovery and robust animal models with high translational potential are crucial. Following peripheral nerve injury reinnervation of denervated target organs is not only achieved by regeneration of the original nerve, but also by collateral sprouting of adjacent intact nerves. In this study motor and sensory recovery was analyzed in a rat model of median nerve injury and repair using distinct functional test. Ten male Wistar rats underwent bilateral median nerve transection. In one forelimb the nerve was repaired using epineurial sutures, while in the contralateral forelimb the nerve remained unrepaired and served as internal control. For 12 weeks post-surgery, the Von Frey Test, the Grasping Test and CatWalk gait analysis were performed weekly. Sensory reinnervation and mechanical allodynia were evaluated with the Von Frey Test in distinct predefined test areas considering the innervation of the forepaws, allowing for indirect assessment of collateral nerve sprouting. Early mechanical allodynia developed within two weeks after median nerve injury in all innervation areas of the forepaw. This was associated with significant alterations of Print Width, Print Area, Duty Cycle, Swing Speed, Swing Time and Stand Index. From week 6 onward late mechanical allodynia paralleled with gait improvements and return of measurable grasping strength on the reconstructed side. The methodology utilized in our study, is feasible to comprehensively assess motor and sensory nerve regeneration paving the way for valid evaluation of future therapeutic strategies in a rat median nerve injury model.